2009
DOI: 10.1177/1470320309352352
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibitors versus angiotensin receptor blockers for diabetic nephropathy: a retrospective comparison

Abstract: Introduction. There are no adequate head-tohead comparisons of angiotensin-converting enzyme (ACE) inhibitors and angiotensin receptor blockers (ARB) in type 2 diabetic patients in spite of some interesting attempts. Furthermore, there are no adequate studies about the effects of ACE inhibitors in type 2 diabetic patients, who are the great majority of diabetic individuals. This study has retrospectively compared the effects of ACE inhibitors and ARBs used to treat diabetic nephropathy in a group of type 2 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…It is unclear whether ACEi target the periostin pathway. While there are no direct head to head comparisons of ACEi and ARBs in patients with diabetes and HF, comparative analyses have suggested that ARBs may be superior to ACEi in the setting of diabetic nephropathy . Studies evaluating strategies that target the periostin pathway, with ARBs or other therapies, may represent a future direction of research among patients with diabetes and HF.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether ACEi target the periostin pathway. While there are no direct head to head comparisons of ACEi and ARBs in patients with diabetes and HF, comparative analyses have suggested that ARBs may be superior to ACEi in the setting of diabetic nephropathy . Studies evaluating strategies that target the periostin pathway, with ARBs or other therapies, may represent a future direction of research among patients with diabetes and HF.…”
Section: Discussionmentioning
confidence: 99%
“…По этой причине обе группы препаратов в обя-зательном порядке входят, в частности, в рекомен-дации Best Practice от 21.10.2013 по лечению диа-бетической нефропатии [4].…”
Section: ñó÷àñíà ôàðìàêîòåðàï³ÿ Modern Pharmacotherapyunclassified
“…However, in hypovolemic patients, ACEIs/ARBs might cause acute renal failure as they cause vasoconstriction of the efferent arteriole; hence, careful attention is required in this group of patients. 9,10 12 On the other hand, non-significant differences in renal protective effects between captopril and nifedipine were observed among non-diabetic CKD patients. 13 The researcher was interested in investigating in-depth the theoretical background and knowledge, clinical attitudes and daily practices of the physicians from different specialties in Iraq regarding the use of RAS blockers in CKD patients.…”
Section: Introductionmentioning
confidence: 97%